1996
DOI: 10.1177/002221949602900204
|View full text |Cite
|
Sign up to set email alerts
|

Community Transition Teams as the Foundation for Transition Services for Youth with Learning Disabilities

Abstract: This article synthesizes descriptions of and recommendations for community transition teams found in research articles, model project reports, and state department documents. The levels, composition, and functions of transition teams are described. Community-level transition teams are shown to be critical support vehicles for helping communities improve their transition programs for youth and adults with learning or other disabilities. Highlights of the changes generated by community teams illustrate their pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Barriers to occupational therapy transition services reported in this study are similar to those reported by Blalock (1996), Everson (1990), Kochhar-Bryant (1999), NICHCY (1993, and Wehman (1990). Access to qualified services providers is perceived as a barrier by 30.8% of respondents in this survey.…”
Section: Discussionsupporting
confidence: 83%
“…Barriers to occupational therapy transition services reported in this study are similar to those reported by Blalock (1996), Everson (1990), Kochhar-Bryant (1999), NICHCY (1993, and Wehman (1990). Access to qualified services providers is perceived as a barrier by 30.8% of respondents in this survey.…”
Section: Discussionsupporting
confidence: 83%
“…Researchers indicated facilitating community involvement and collaboration between transition programmes and other community organizations are helpful to improve transition outcomes. In particular, involving employers in transition process are crucial in delivering effective transition services (Blalock, ; Oertle & Trach, ; Sabbatino & Macrine, ).…”
Section: Discussionmentioning
confidence: 99%
“…Though numerous documents are available to assist public agencies to engage participating agencies in transition planning (see Benz, Lindstrom & Halpern, 1995;Blalock, 1996;deFur, 1999;deFur & Patton, 1999;Everson, 1993;Everson & Guillory, 1998;Wehman, 1996), state and local education agencies consistently appear to deliver transition services without the benefit of these agencies in the planning, identification and delivery of the programs, services, and supports. A study by Foley and Mundschenk (1997) provides an explanation for this apparent disconnect between secondary education practitioners and participating agency personnel.…”
Section: Transition Services Participantsmentioning
confidence: 99%